15-oxo-ETE-induced internal carotid artery constriction in hypoxic rats is mediated by potassium channels - Wang, D; Liu, Y; Lu, P; Zhu, D; Zhu, Y (Physiological research, 2016)
Our own study as well as others have previously reported that hypoxia activates 15-lipoxygenase (15-LO) in the brain, causing a series of chain reactions, which exacerbates ischemic stroke. 15-hydroxyeicosatetraenoic acid (15-HETE) and 15-oxo-eicosatetraenoic acid (15-oxo-ETE/15-KETE) are 15-LO-specific metabolites of arachidonic acid (AA). 15-HETE was found to be rapidly converted into 15-oxo-ETE by 15-hydroxyprostaglandin dehydrogenase (15-PGDH) in some circumstances. We have demonstrated that 15-HETE promotes cerebral vasoconstriction during hypoxia. However, the effect of 15-oxo-ETE upon the contraction of cerebral vasculature remains unclear. To investigate this effect and to clarify the underlying mechanism, we performed immunohistochemistry and Western blot to test the expression of 15-PGDH in rat cerebral tissue, examined internal carotid artery (ICA) tension in isolated rat ICA rings. Western blot and reverse transcription polymerase chain reaction (RT-PCR) were used to analyze the expression of voltage-gated potassium (Kv) channels (Kv2.1, Kv1.5, and Kv1.1) in cultured cerebral arterial smooth muscle cells (CASMCs). The results showed that the levels of 15-PGDH expression were drastically elevated in the cerebral of rats with hypoxia, and 15-oxo-ETE enhanced ICA contraction in a dose-dependent manner. This effect was more significant in the hypoxic rats than in the normoxic rats. We also found that 15-oxo-ETE significantly attenuated the expression of Kv2.1 and Kv1.5, but not Kv1.1. In conclusion, these results suggest that 15-oxo-ETE leads to the contraction of the ICA, especially under hypoxic conditions and that specific Kv channels may play an important role in 15-oxo-ETE-induced ICA constriction.
Keywords: vazokonstrikce; Carotid Artery, Internal; hydroxyprostaglandindehydrogenasy; hypoxie; In Vitro Techniques; Hypoxia; Vasoconstriction; Arachidonic Acids; Glyburide; mužské pohlaví; Rats, Wistar; kyseliny arachidonové; techniky in vitro; 4-aminopyridin; Hydroxyprostaglandin Dehydrogenases; zvířata; Tetraethylammonium; glibenklamid; Potassium Channels; draslíkové kanály; tetraethylamonium; potkani Wistar; 4-Aminopyridine; arteria carotis interna; Male; Animals